2019
DOI: 10.13057/biodiv/d201224
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Species diversity of mangrove in Kutai National Park, East Kalimantan, Indonesia

Abstract: Abstract. Poedjirahajoe E, Sulityorini IS, Komara LL. 2019. Short Communication: Species diversity of mangrove in Kutai National Park, East Kalimantan, Indonesia. Biodiversitas 20: 3641-3646. Kutai National Park (KNP) in East Kalimantan, Indonesia is blessed with natural mangrove forests. However, there is only very little information relating to the species composition and mangrove diversity. Therefore, this study was conducted to assess the mangrove tree species diversity and richness in Kutai National Park,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The actinomycetes biodiversity in mangrove ecosystems, in particular in Indonesia, is still underexplored (Li et al 2019;Hamed et al 2021). It is unfortunate because, with a total area of 4.25 million ha, mangrove forests in Indonesia are the largest globally, representing 20% of the world's mangroves (Poedjirahajoe et al 2019). One of the mangrove ecosystems in Indonesia is Mangrove Center Tuban, located in the coastal area of Jenu Village, Tuban, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The actinomycetes biodiversity in mangrove ecosystems, in particular in Indonesia, is still underexplored (Li et al 2019;Hamed et al 2021). It is unfortunate because, with a total area of 4.25 million ha, mangrove forests in Indonesia are the largest globally, representing 20% of the world's mangroves (Poedjirahajoe et al 2019). One of the mangrove ecosystems in Indonesia is Mangrove Center Tuban, located in the coastal area of Jenu Village, Tuban, Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies on the coasts of major cities, namely Jakarta Bay and Muara Kapuk, have identified 5 to 9 mangrove species (Rumondang et al 2021;Sari et al 2019). The number of mangrove species found in remote areas with natural mangrove forests is considerably higher, as evidenced by studies in Mimika Papua (66 species), Segara Anakan Cilacap, Central Java (16 species) and Kutai National Park, East Kalimantan (17 species) (Poedjirahajoe et al 2019;Setyadi et al 2021;Widyastuti et al 2018). Excellent water and sediment quality, low environmental pollution, and the absence of illegal logging are all factors that contribute to the optimal growth of mangrove forests in remote coastal areas.…”
Section: Mangrove Community Structurementioning
confidence: 96%